Activity dependent internalization of the glutamate transporter GLT-1 requires calcium entry through the NCX sodium/calcium exchanger. (February 2019) - Ibáñez, Ignacio; Bartolomé-Martín, David; Piniella, Dolores; Giménez, Cecilio; Zafra, Francisco
Abstract: GLT-1 is the main glutamate transporter in the brain and its trafficking controls its availability at the cell surface, thereby shaping glutamatergic neurotransmission under physiological and pathological conditions. Extracellular glutamate is known to trigger ubiquitin-dependent GLT-1 internalization from the surface of the cell to the intracellular compartment, yet here we show that internalization also requires the participation of calcium ions. Consistent with previous studies, the addition of glutamate (1 mM) to mixed primary cultures (containing neurons and astrocytes) promotes GLT-1 internalization, an effect that was suppressed in the absence of extracellular Ca 2+ . The pathways of Ca 2+ mobilization by astrocytes were analyzed in these mixed cultures using the genetically encoded calcium sensor GCaMP6f. A complex pattern of calcium entry was activated by glutamate, with a dramatic and rapid rise in the intracellular Ca 2+ concentration partially driven by glutamate transporters, especially in the initial stages after exposure to glutamate. The Na + /Ca 2+ exchanger (NCX) plays a dominant role in this Ca 2+ mobilization and its blockade suppresses the glutamate induced internalization of GLT-1, both in astrocytes and in a more straightforward experimental system like HEK293 cells transiently transfected with GLT-1. This regulatory mechanism might be relevant to control the amount of GLT-1 transporter at the cell surface in conditions like ischemia or traumatic brain injury, where extracellular concentrations of glutamate are persistently elevated and they promote rapid Ca 2+ mobilization. Highlights: Glutamate triggered internalization of GLT-1 requires extracellular calcium. Glutamate transport through GLT-1 activate diverse calcium channels. Glutamate activates the NCX sodium calcium exchanger, which in turn triggers GLT-1internalization.